Problems of Rejection of Applications for Prospective Marriage Dispensation in Islamic Law - Hertasmaldi, Hertasmaldi; Hafiz, Abdul; Mardianton, Mardianton (Samara: Journal of Islamic Law and Family Studies, 2023)
This article discusses the judge's decision in rejecting the application for marriage dispensation which had been submitted and registered at the Registrar's Office of the Painan Religious Court with Number: 68/Pdt.P/2021/PA.Pn, that the Petitioner intended to carry out the marriage of the Petitioner's 18-year-old biological child with a 46-year-old man. The researcher uses the Library Research (library) research method. The researcher describes a structured research procedure, namely the research approach. Because what is being studied is written text in the form of a corpus (data used as a source of research material). The research information that becomes primary data is the decision of the judge of the Painan religious court, while the secondary data is data obtained from written sources, library materials including statutory regulations, scientific literature, books and articles. , and journals. The results of the research can be concluded that the judge's decision can be correct because the judge adheres firmly to educational, and psychological aspects, as well as the potential for disputes in the household that will be fostered for children. In Islamic law, it is permitted by fiqh law and the values ​​aimed at implementing sharia.